(untitled) (Ushuluddin International Conference (USICON), 2017)
The study of the theoretical history of Maqshid is based on several reasons. First, one implication of the theological view of Muslims that the Qur’an is always relevant for every time and place is the development of a methodological interpretation significantly along with the acceleration of the development of socio-cultural conditions and human civilization. It is reasonable if Syahrur said that the Qur’an needs to be interpreted in accordance with the demands of the contemporary era. Second, that Islam is faced with permanent problems, namely the limited number of texts (al-Qur’an and al-Hadith), while the various events and dynamics of society are constantly rolling out and creating more complicated and complex problems. Unfortunately, the response that often comes to the surface is apologetic defensive and counter-productive actions. For some of these considerations, the conception of Jasser Auda, a contemporary Muslim thinker from Egypt, about Maqashidal-Shari